Growth and guaiacol production of species of Alicyclobacillus isolated from the South African fruit processing environment - Smit, Yvette (Stellenbosch : University of Stellenbosch, 2009)
Thesis (Msc Food Sc (Food Science))--University of Stellenbosch, 2009.